2015
DOI: 10.5665/sleep.4510
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inflammatory Activity in Nonobese Patients with Coronary Artery Disease and Obstructive Sleep Apnea

Abstract: OSA with ODI ≥ 5 was independently associated with increased inflammatory activity in this nonobese CAD cohort. The intermittent hypoxemia, rather than the number of apneas and hypopneas, appears to be primarily associated with enhanced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…57 Both inflammation and oxidative stress have been known to play major roles in the pathogenesis of OSAS. 52,58 These findings showed that inflammatory markers play a potential role in a mechanism of CVD via inflammation, and oxidative stress for OSAS. There is also evidence that OSAS has some relationship with the development of CVD, coronary artery disease, 22 Our findings suggested that RDW levels increased in the presence of OSAS and CVD, which might be an independent predicting factor in patients with OSAS having CVD.…”
Section: Discussionmentioning
confidence: 93%
“…57 Both inflammation and oxidative stress have been known to play major roles in the pathogenesis of OSAS. 52,58 These findings showed that inflammatory markers play a potential role in a mechanism of CVD via inflammation, and oxidative stress for OSAS. There is also evidence that OSAS has some relationship with the development of CVD, coronary artery disease, 22 Our findings suggested that RDW levels increased in the presence of OSAS and CVD, which might be an independent predicting factor in patients with OSAS having CVD.…”
Section: Discussionmentioning
confidence: 93%
“…44 Studies of a sleep apnea cohort have documented higher concentrations of proinflammatory cytokines such as tumor necrosis factor, interleukin-1, and interleukin-6 in patients with sleep apnea compared with controls; however, the association of these markers with AHI has not been universal. 45,46 Considering that these biomarkers have been linked to impaired endovascular and cognitive functioning, 47,48 abatement of these inflammatory biomarkers following treatment whether by using CPAP or MAD 49,50 may infer additional benefit beyond the rectification of respiratory abnormalities by either modality.…”
Section: Discussionmentioning
confidence: 99%
“…OSA independently associated with increase of inflammatory biomarkers CRP, TNF-α and IL-6 activity related to intermittent hypoxia (Thunstrom et al, 2015). Leon-Cabrera and colleagues found decrease in IL-10 levels were significantly related to increased Apnea-Hypopnea Index (AHI), hyperinsulinemia, and insulin resistance than morbid and control individuals without OSA.…”
Section: Intermittent Hypoxia and Inflammationmentioning
confidence: 95%
“…At same time the process of hypoxia/reoxygenation would affect cell components, such as mitochondrial function, which increased production of reactive oxygen species (ROS) (Suzuki et al, 2006). Oxidative stress as important inflammatory activator component in OSA (Thunstrom et al, 2015). That adipose tissue considered as major source of cytokines/adipokines whether they are produced in obesity per se and/or because of OSA (Lavie & Polotsky, 2009) (Figure.1.).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation